Analisis Rasio Keuangan Terhadap Kinerja Keuangan Perusahaan Food And Beverage Yang Terdaftar Di Bursa Efek Indonesia Pada Tahun 2020-2024 - Mahesa Raihan Akbar Rizqulloh; Hayatul Maspufah; Musaiyadi . (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to analyze the effect of Net Profit Margin (NPM), Current Ratio (CR), and Debt to Asset Ratio (DAR) on Return on Assets (ROA) as a measure of company performance in Food and Beverage companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The study employed secondary data obtained from annual financial statements and used a purposive sampling technique. Data were analyzed using multiple linear regression with SPSS, including descriptive statistical analysis, classical assumption tests, coefficient of determination (R²), F-test, and t-test. The results indicate that NPM, CR, and DAR simultaneously have a significant effect on ROA, while partially only NPM has a significant effect on ROA, whereas CR and DAR do not have a significant effect on ROA. Furthermore, the coefficient of determination shows that variations in company performance can be explained by NPM, CR, and DAR, while the remaining variation is influenced by other factors outside the research model